2022
DOI: 10.1111/psyp.14066
|View full text |Cite|
|
Sign up to set email alerts
|

Uncovering the effects of bilingual language control on rational decisions: An ERP study

Abstract: A growing body of research suggests that the language in which bilinguals make decisions affects the rationality of such decisions. Furthermore, bilinguals constantly confront cross‐language interference that requires complex language control processes to resolve this competition. However, the relationship between language control and decision‐making is unclear. In the current study, we analyze electrophysiological and behavior data elicited from two groups of Chinese‐English bilinguals. One group was trained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Paired‐sample t‐ tests revealed that the participants' L1 was significantly stronger than their L2 in listening ( t = 16.11, p < .001), speaking ( t = 19.24, p < .001), reading ( t = 17.37, p < .001), and writing ( t = 11.97, p < .001). These self‐ratings and OPT scores are similar to intermediate Chinese–English bilinguals tested in prior research (Liu et al, 2021 ; Liu, Liang, et al, 2016 ; Liu, Schwieter, Wang, et al, 2022 ), implying that the individuals have unequal proficiency between their two languages.…”
Section: Methodssupporting
confidence: 80%
See 3 more Smart Citations
“…Paired‐sample t‐ tests revealed that the participants' L1 was significantly stronger than their L2 in listening ( t = 16.11, p < .001), speaking ( t = 19.24, p < .001), reading ( t = 17.37, p < .001), and writing ( t = 11.97, p < .001). These self‐ratings and OPT scores are similar to intermediate Chinese–English bilinguals tested in prior research (Liu et al, 2021 ; Liu, Liang, et al, 2016 ; Liu, Schwieter, Wang, et al, 2022 ), implying that the individuals have unequal proficiency between their two languages.…”
Section: Methodssupporting
confidence: 80%
“…To assess L1 and L2 proficiency levels of the participants, we adopted the Oxford quick placement test (OPT; Geranpayeh, 2003 ; Liu, Schwieter, Liu, et al, 2022 ; Liu, Schwieter, Wang, et al, 2022 ), and asked individuals to rate their language abilities on a six‐point scale in which “1” indicated no knowledge and “6” indicated perfect knowledge (Liu et al, 2021 ). A one‐way ANOVA was next conducted for each polymorphism and revealed no significant differences between genotypes in age, age of L2 acquisition, self‐ratings of language abilities, and OPT scores (see Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations